H književnosti enega jezika - Grdina, Igor (Jezik in slovstvo, 2016)
The medieval feudal tripartite social order of clerics, warriors, and farmers and craftsmen also produced language division into Latin, German and Slovenian. The main cohesive means became the Christian religion, which, due to the universality of the salvific message, demanded the use of Slovenian in sermons, sacrament of penance and basic prayers, and thus (co-)shaped language communities. The article shows the spread of spoken and written Slovenian in all three orders and for all uses from the Middle Ages, through the Reformation, to the Enlightenment circle of Zois and Pohlin.
Keywords: Slovene; slovenščina; zgodovina; history; družbeni sloji; Christianity; krščanstvo